Use of blends of glove waste and natural rubber in rubber products manufacture - Seneviratne W M G; Abeykoon A M C; Sarath Kumara P H (Journal of the Rubber Research Institute of Sri Lanka, 1996)
Substantial amount of defective examination gloves are rejected in glove manufacturing factories in Sri Lanka. These glove rejects cause severe environmental hazards. A series of experiments were therefore carried out to investigate the possibility of recycling these glove rejects and using them as a blend or a filler in the manufacture of rubber products. The results of the experiments indicate that appreciable quantity of recycled glove waste can be blended with NR to give properrties comparable to that obtained from NR alone.
Keywords: Cure characteristics; Glove crumbs; Glove waste; Mastication; NR blends; Peptiser; Reclaiming; Recycling